Sunflower - SHARP, MARILYN; MARILYN SHARP (London Pan Books, 1979)
Someone high up in government has become a deadly security leak and there is only one way to track him down - kidnap the President's four-year-old daughter and force his hand.
Keywords: This book documents the growth of a sunflower from a seed to a tall; resilience, positivity, and growth